2013
DOI: 10.1002/app.39883
|View full text |Cite
|
Sign up to set email alerts
|

In situ small angle X‐ray scattering study on structural evolution of crosslinked polytetrafluoroethylene during deformation

Abstract: The structural evolution of virgin and crosslinked polytetrafluoroethylene (PTFE) during stretching was studied by in situ synchrotron small-angle X-ray scattering (SAXS). Both yield and tensile stress of crosslinked PTFE increased with increasing crosslinking density. During stretching, for virgin PTFE, amorphous chains gradually turned to tensile direction at early stage, perpendicularly arranged lamellar stacks appeared at high strains (>140%). While for crosslinked PTFE, lamellar structure was observed eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…18 However, SiO 2 is an insulator and a lot of work has been done to expand the applications of insulator SiO 2 as a filler to improve the processability of PANI. 19 -23 Corrosion protective coatings on mild steel surfaces by the electrochemical deposition of conducting polymers have been extensively studied. 24 -28 These types of coating lack the long-lasting ability of metals in a corrosive medium.…”
Section: Introductionmentioning
confidence: 99%
“…18 However, SiO 2 is an insulator and a lot of work has been done to expand the applications of insulator SiO 2 as a filler to improve the processability of PANI. 19 -23 Corrosion protective coatings on mild steel surfaces by the electrochemical deposition of conducting polymers have been extensively studied. 24 -28 These types of coating lack the long-lasting ability of metals in a corrosive medium.…”
Section: Introductionmentioning
confidence: 99%
“…Though these values may not be the optimal ratios for conductivity, PANI/TiO 2 (or PANI/SiO 2 ) also exhibits relatively high conductivity properties (several times higher than that of pristine PANI). Moreover, we found that the conductivities of PANI/TiO 2 (or PANI/SiO 2 ) composites always vary in an order of magnitude 1,2,13,16 and the lowest conductivity value of PANI/TiO 2 2SiO 2 composites (PANI-60, 2.840E24 S/m without additional pressure; PANI-15, 5.452E24 S/m with additional pressure of 500 g/cm 2 ) is higher than that of PANI/TiO 2 and PANI/SiO 2 , respectively. This significant enhancement in conductivity of PANI/TiO 2 2SiO 2 is due to the instinct properties of the TiO 2 2SiO 2 composite rather than its percentage in the composites.…”
Section: Articlementioning
confidence: 86%
“…However, these small fillers are severely aggregated and some time can diminish the extent of conjugation of PANI macromolecules, thus their conductivities are restricted. 15,16 Until now, the microstructure design of high performance PANI remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The structures of the soft segment and especially of the hard segment affect the properties because they act together on the degree of phase separation, crystallization, morphology and hydrogen bonds. [6][7][8] Hard domains formed by self-organization and physical crosslinks determine the morphology of the phases. This can be influenced by the structure and length of the hard segments, which directly determine the physical properties of the polyurethane material.…”
Section: Introductionmentioning
confidence: 99%